Pengembangan Media Pembelajaran Matematika Berbasis Android Terhadap Kemampuan Komunikasi Matematis siswa Kelas IV SD - Putri, Gita Fajar; Masniladevi, Masniladevi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2017)
This research aims to produce android-based mathematics learning media for elementary school. This research is based on the results of observations in the field that students' ability to communicate mathematics mathematically is still lacking. In the research conducted is research with the type of development research (Research and Development) with ADDIE models, namely Analysis (analysis), Design (design), Development (development), Implementation (implementation), and Evaluation (evaluation). Learning media that have been developed will be assessed and validated by experts who are competent in their fields. The instrument used in this study is a questionnaire in the form of teacher responses and student responses to the android-based mathematics learning media. Results: 1) The author has produced an Android-based mathematics learning media on flat waking circumference material for fourth grade students of SD / MI, 2) Expert judgment in material validation and media validation which gets a percentage of 95% at very valid intervals, 3) responses Grade IV SD / MI students on the practicality of media based on Android mathematics learning obtained an evaluation percentage of 87%. This value is at very very practical intervals.